2020
DOI: 10.1371/journal.pone.0228325
|View full text |Cite
|
Sign up to set email alerts
|

Hemocyanin of the caenogastropod Pomacea canaliculata exhibits evolutionary differences among gastropod clades

Abstract: Structural knowledge of gastropod hemocyanins is scarce. To better understand their evolution and diversity we studied the hemocyanin of a caenogastropod, Pomacea canaliculata (PcH). Through a proteomic and genomic approach, we identified 4 PcH subunit isoforms, in contrast with other gastropods that usually have 2 or 3. Each isoform has the typical Keyhole limpet-type hemocyanin architecture, comprising a string of eight globular functional units (FUs). Correspondingly, genes are organized in eight FUs coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…The number of internal introns of Tectipleura hemocyanins is greater than that found in hemocyanin genes of Pomacea canaliculata , which comprise 21 to 26 internal introns per gene according to Chiumiento et al . [ 21 ]. The P. canaliculata gene structures are intentionally omitted from Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of internal introns of Tectipleura hemocyanins is greater than that found in hemocyanin genes of Pomacea canaliculata , which comprise 21 to 26 internal introns per gene according to Chiumiento et al . [ 21 ]. The P. canaliculata gene structures are intentionally omitted from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Only recently, Chiumiento et al . [ 21 ] showed that exon–intron structures of four hemocyanin genes of the caenogastropod Pomacea canaliculata differ not only from those of Lepetellida but also vary from each other. Furthermore, they contain a much larger number of introns than those known from Vetigastropoda or Cephalopoda (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rhogocytes have been described in different gastropod molluscs [48,[68][69][70], including P. canaliculata [71], and have been proposed to be involved in several functions, including metabolism and/or detoxification of metal ions [50,[72][73][74][75], cellular defence [68,76,77] and the production of haemocyanin [48,[78][79][80][81][82], which, in its specific multimeric form, was detected in association with rhogocytes by TEM analysis in Lymnaea stagnalis and Haliotis tubercolata [49,78]. TEM observations have also documented the structure of isolated or tissue haemocyanin in P. canaliculata [19,83,84]. In our experimental conditions, we identified haemocyanin by proteomic analysis but not by TEM.…”
Section: Discussionmentioning
confidence: 99%